The identity of Stranvaesia microphylla (Rosaceae, Maleae) from Vietnam - Wang, Long-Yuan; Feng, Hui-Zhe; Guo, Wei; Fan, Qiang; Chen, Su-Fang; Liao, Wen-Bo (Phytotaxa, 2018)
Critical examination of herbarium specimens (including type materials) has shown that Stranvaesia microphylla described from Vietnam is conspecific with Photinia davidiana var. undulata (≡Stranvaesia davidiana var. undulata), which is widely distributed in China. Therefore, S. microphylla is reduced as a synonymy of P. davidiana var. undulata. Additionally, one new combination has been proposed and one lectotype has been designated here.